Penerapan Discovery Learning Menggunakan Puzzle Untuk Meningkatkan Hasil Belajar Siswa (Journal of Madrasah Studies, 2024)
This study aims to determine student learning outcomes at MIN 1 Medan by learning discovery learning models with the help of puzzle props and Jigsaw strategies motivated by an interest in mathematics lessons considered complex, unreachable by thinking, and not valid for life. The research method used is classroom action research, which uses quantitative and qualitative data analysis techniques. The application of this model can increase the average value of student learning outcomes, namely in cycle I by as much as 56.72 and average increase in cycle II by as much as 79.21, and can increase the percentage of students' learning mastery as much as 14.28% in the second cycle I, and increased to 82.15% in Cycle II.